Short Interest and the Cross-Section of S&P500 Share Returns - Cumming, Kyle (Department of Finance and Tax, 2023)
This study aims to investigate the cross-sectional relationship between short interest and excess returns of the constituent securities of the Standard and Poor's 500 Index on a monthly basis. Short interest data is defined in relation to both trading volume and equity float for an 84-month period between January 2015 and December 2021 to examine the expected negative relationship. The use of the Fama-Macbeth (1973) method produces mixed empirical findings. The results of the short interest ratio do not support the findings of prior research, finding no significant relationship between the two variables. The short float ratio, however, produces a significantly positive relationship at the 10% level, supporting the “contrarian view”. An increase in the short float ratio of 1% leads to a 19.6 basis point increase in excess return in the subsequent month. Overall, our results for the short interest ratio support the efficient market hypothesis. In contrast, the short float ratio serves as a bullish indicator.